Waste to Energy Utilization Technology Study in Padang City - Wendi Surdinal; Rizki Aziz; Vera Surtia Bachtiar; Muhammad Fadhli Ajis (CIVED, 2025)
Solid waste management in Padang City is problematic due to the annual increase in waste generation, which leads to various environmental issues. This study aims to predict the most profitable waste-to-energy (WtE) treatment methods from technical and environmental perspectives that can alleviate these issues in Padang City. The study begins with analyzing solid waste generation, composition, and characteristics. Additionally, the amount of incoming waste for thermal planning is projected based on projected generation and population. The environmental implications were assessed using the LCA (Life Cycle Assessment) method. Various waste treatment methods' technical and environmental viability was evaluated, focusing on projected waste generation in 2031, estimated at 929 tons/day. The analysis of technical aspects revealed that thermal processing of mixed waste gasification is the most profitable option, requiring only 5,101 m2 of land and capable of producing 188 GWh/year while achieving the lowest LCA Single Score of 5.82E+04 Conversely, anaerobic digesters and RDF processing generate 120 GWh and 47 GWh of electrical energy, respectively, with Single Score LCA of 4.25E+10 Pt and 7.74E+09 Pt. However, the environmental impact of WtE is the most significant, primarily due to its contribution to global warming. Global warming is predominantly attributed to carbon monoxide (CO) compounds, with carbon dioxide (CO₂) being the primary emission responsible for the observed increase in global temperature.